Violence Suffered by the Main Character in Jay Asher’s Thirteen Reasons Why - OKTAVIANI, VIA (English Literature Study Program, 2023)
Violence still often occurs both in the school environment and outside the school. Women have always been the victims of violence perpetrated by men because women are considered inferior beings. Jay Asher's novel Thirteen Reasons Why (2017) tells about thirteen reasons why Hannah Baker committed suicide, which were told in a recording. The researcher aimed to analyze the violence that Hannah Baker suffered in this study and the way she was affected by the violent acts using the theory of violence developed by Galtung (1990). The main data were obtained from Jay Asher's novel entitled Thirteen Reasons Why in the form of words, phrases, and sentences. After the data had been collected, the researcher started to classify them. The results revealed that Hannah experienced psychological, physical, and sexual violence. She was also treated very badly by people in her surroundings; one of whom even raped her. Thus, in the end she committed suicide because she could not bear the pressure in her life. The readers should comprehend the risks of teen stress and violence by examining the main topic and data, as experienced by Hannah Baker. For future studies, the researcher's suggestion was to use other viewpoints from the book and other theories of violence.